Digitalization of Online Business to Enhance Export-Import Services: An Islamic Economic Perspective at PT. Hansa Meyer Global Indonesia - Oktarizal, Tania (Li Falah: Jurnal Studi Ekonomi dan Bisnis Islam, 2024)
The economy is a fundamental human activity aimed at fulfilling the instinct to survive. As time progresses and society evolves, human needs have become increasingly complex, driving some to produce goods and offer services to meet consumer demands. The shift in the business world during the Industrial Revolution 4.0 is deeply intertwined with technology. Even the simplest businesses are now linked to technology, such as buying and selling, which often uses digital money. It opens up opportunities for digital transformation in new businesses in the digital and technology sectors, which are growing rapidly in Indonesia. This research is a field study using both primary and secondary data. The qualitative research method employed includes data collection through interviews, observations, and documentation. The analysis of the data reveals the implementation of E2Log digitization in export-import goods delivery services at PT. Hansa Meyer Global Indonesia includes features that facilitate company operations, such as data analysis, inventory management, shipping routes, tracking, and payment management. The digitization of E2Log enhances revenue and profitability through resource optimization, timely decision-making, and customer satisfaction. Additionally, from an Islamic economic perspective, the use of E2Log digitization aligns with Islamic economic principles, including fairness, avoiding usury, and social responsibility.